Bertrand Game Under Cost Function1. (28th August 2018) - Dube, Partha Pratim
Abstract : This paper analyses price competition in the case of monopoly and duopoly considering cost function under the minimum money expensed with demand probability and shows the existence of pure strategy Nash equilibrium of a Bertrand game. It also finds price strategies of two firms to earn maximum profits in a Bertrand game.